Avaliação dos aspectos fisiológicos, bioquímicos e moleculares no feijoeiro comum ( phaseolus vulgaris) com o uso do indutor biótico trichoderma harzianum contra sclerotinia sclerotiorum - Brandão, Renata Silva (2012)
The fungus Trichoderma spp., is a microorganism naturally found in soil, which presents an important ecological function, as part of the decomposition and mineralization of plant residues, contributing to the availability of nutrients to plants. It is considered also a natural biofungicide, which reduces up to 100% the chances of achieving any fungus culture. The fungus Trichoderma is a fast growing, hence the advantage of use as a biocontrol agent in large scale, produces a variety of antifungal metabolites, including antibiotics and enzymes that degrade the cell wall of certain pathogens, is related to growth promotion in plants and the induction of resistance. The fungus Sclerotinia sclerotiorum is the etiological agent of the disease known as white mold in different cultures, such as soft rot, white mold, tipping pre-emergent and post-emergent plants. It is estimated that about 300 plant species are susceptible to S. sclerotiorum, such as the common bean (Phaseolus vulgaris) and soybean (Glycine max), both of great economic importance. Thus, this work needs to evaluate physiological, biochemical and molecular in common bean using the inductor Trichoderma harzianum against Sclerotinia sclerotiorum. Three isolates of T. harzianum and one isolate S. sclerotiorum were selected for inoculation in bean plants. In plants inoculated with isolates of T. harzianum 475/02 was possible to observe higher values related to the physiological aspects, as the plants inoculated with T. harzianum 479/01 had the highest enzyme activities in the R5 stage. Treatments with more pathogen T. harzianum showed the highest expression of the genes of interest, demonstrating greater efficiency when the two fungi act together.